University students’ attitude towards a non-standard instructional proposal for introducing eigentheory - Piroi, Margherita (LUMAT-B: International Journal on Math, Science and Technology Education, 2024)
In this paper, I present the responses of first-year engineering students to a questionnaire exploring their evaluation of a novel teaching sequence used to introduce eigentheory in a linear algebra course. I analyse these responses using the notion of the scale of levels of didactic codetermination, as conceived and used in the anthropological theory of the didactic, to study the ecology of mathematical practices in a particular institution. Specifically, I show how the recurring themes in students’ responses are likely to be rooted in higher levels of the scale, such as that of the school and pedagogy. This implies that it is necessary to act at these levels as well in order to change students’ attitudes towards non-standard didactic approaches.